(x, y ) → (- 1, 3 )
The solution to the system of equations is the point of intersection of the 2 lines
From the graph, that is (x, y ) → ( - 1, 3 )
We can confirm by solving algebraically
Since both equations express y in terms of x we can equate the right sides
- x + 2 = - 6x - 3 ( add 6x to both sides )
5x + 2 = - 3 ( subtract 2 from both sides )
5x = - 5 ( divide both sides by 5 )
x = - 1
substitute x = - 1 into either of the 2 equations for y-coordinate
y = - x + 2 = 1 + 2 = 3
solution is (x, y ) → (- 1, 3 )